Determinan Market Share Industri Keuangan Non Bank Syariah Indonesia - Wahyu Syarvina; Andri Soemitra; Zuhrinal Nawawi (Jurnal Riset Akuntansi dan Bisnis, 2023)
The market share of the non-Islamic non-bank financial industry is moving slowly, incomparable with Indonesia's Muslim population which reaches 87%. The purpose of this study was to determine the effect of assets and equity on the market share of the Islamic non-bank financial industry for the period 2017 to 2021. This research method uses a quantitative approach with an associative method. The sampling technique was carried out by researchers with special considerations (purposive sampling), namely the sampling technique with special considerations so that what is suitable as a sample. The data analysis technique used in this research is to carry out quantitative analysis expressed in numbers which in the calculations use statistical methods assisted by the statistical data processing program SPSS version 26 for Windows so that it can be seen whether there is an effect of several independent variables on the dependent variable. . From the results of data processing using SPPS, the results show that assets and equity do not affect the market share of the non-sharia financial industry in Indonesia for the period 2017 to 2021